2017
DOI: 10.1093/jmicro/dfx027
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional observations of morphology of low-angle boundaries in ultra-low carbon lath martensite

Abstract: The lath martensite structure contains hierarchical substructures, such as blocks, packets and prior austenite grains. Generally, high-angle grain boundaries in the lath martensite structure, i.e. block boundaries, are correlated to mechanical properties. On the other hand, low-angle grain boundaries play an important role in morphological development. However, it is difficult to understand their nature because of the difficulty associated with the characterization of the complex morphologies by two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The micrographs show that the specimens consist of fully lath martensite structures. Using the line intercept method, the sizes of the prior austenite grain in the ULC and LC structures were measured to be 107 μm 13) and 100 μm, respectively. In ULC lath martensite, a block, or a region with similar grey values, has a plate-like shape.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The micrographs show that the specimens consist of fully lath martensite structures. Using the line intercept method, the sizes of the prior austenite grain in the ULC and LC structures were measured to be 107 μm 13) and 100 μm, respectively. In ULC lath martensite, a block, or a region with similar grey values, has a plate-like shape.…”
Section: Resultsmentioning
confidence: 99%
“…In ULC lath martensite, we already reported that there are type II blocks, which are enclosed in the type I blocks. 13) However, the ULC type II blocks are not the same as the LC type II blocks since most of the ULC type II blocks belong to different CP groups than the CP group of adjacent type I blocks. 11,13) In the LC specimen, some type II blocks belonging to different CP groups are enclosed in the coarse packet as shown as the white regions in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations